Regional competitiveness, university spillovers and entrepreneurial activity - David B. Audretsch; Marcel Hülsbeck; Erik E. Lehmann (University of Augsburg, Chair of Management and Organization, 2010)
This study examines the impact of regional competitiveness on the innovative activity of entrepreneurial firms. Based on a unique and hand collected data set of publicly listed high technology start-ups and university regions, this paper tests how regional competitiveness and university spillovers affect the innovation behaviour of entrepreneurial firms. The results provide strong evidence that regional competitiveness and university spillovers are strong complements in fostering innovation activity of entrepreneurial firms. However, the results also raise the question whether incentives for universities and their actors might lead to crowding out effects.
Keywords: M13; L20; R30; 650; Regional Competitiveness; University Spillovers; Entrepreneurship